5-Keto-D-fructose production from sugar alcohol by isolated wild strain Gluconobacter frateurii CHM 43 - Adachi, Osao (2020)
Gluconobacter frateurii: CHM 43 have D-mannitol dehydrogenase (quinoprotein glycerol dehydrogenase) and flavoprotein D-fructose dehydrogenase in the membranes. When the two enzymes are functional, D-mannitol is converted to 5-keto-D-fructose with 65% yield when cultivated on D-mannitol. 5-Keto-D-fructose production with almost 100% yield was realized with the resting cells. The method proposed here should give a smart strategy for 5-keto-D-fructose production.